A Rare Case of Congenital Rubella Syndrome - Vishwanath Hesarur (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
Introduction: Congenital rubella syndrome (CRS) is a consequence of rubella infection that can occur when the virus is transmitted in utero during maternal primary infection. It still affects 110,000 children around the world. It has a wide spectrum of presentation which ranges from silent viremia to spontaneous abortions, blindness, deafness, congenital heart disease, and mental retardation. Case Report: Here, we report a case of CRS in a girl aged 8 years who presented with congenital cataract, severe post ductal coarctation of aorta with patent ductus arteriosus and bilateral sensory neural hearing impairment. Conclusion: We present a case report of congenital rubella syndrome (CRS); though uncommon nowadays, it is still present in India. The main characteristics of our case report were congenital cataract, severe post ductal coarctation of aorta with patent ductus arteriosus and sensory neural hearing impairment. This case is reported to highlight the importance of vaccination by which rubella infection can be eradicated.